2021
DOI: 10.1186/s40486-020-00126-9
|View full text |Cite
|
Sign up to set email alerts
|

All-soft multiaxial force sensor based on liquid metal for electronic skin

Abstract: Electronic skin (E-skin) capable of detecting various physical stimuli is required for monitoring external environments accurately. Here, we report an all-soft multiaxial force sensor based on liquid metal microchannel array for electronic skin applications. The proposed sensor is composed of stretchable elastomer and Galinstan, a eutectic gallium-indium alloy, providing a high mechanical flexibility and electro-mechanical durability. Liquid metal microchannel arrays are fabricated in multilayer and positioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Due to its natural advantages of high electrical conductivity, high thermal conductivity, fluidity, and controllable deformation, LM has been widely used in switches [39][40][41][42][43], reconfigurable antennas [48][49][50][51][52][53][54][55], microwave devices [10][11][12][13], sensors [57][58][59][60], and wearable devices and flexible circuits [62][63][64]. Gallium-based LM can be used as a substrate integrated waveguide switch [39] and can also be used as a thermal switch controlling heat transfer spatially and temporally [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its natural advantages of high electrical conductivity, high thermal conductivity, fluidity, and controllable deformation, LM has been widely used in switches [39][40][41][42][43], reconfigurable antennas [48][49][50][51][52][53][54][55], microwave devices [10][11][12][13], sensors [57][58][59][60], and wearable devices and flexible circuits [62][63][64]. Gallium-based LM can be used as a substrate integrated waveguide switch [39] and can also be used as a thermal switch controlling heat transfer spatially and temporally [42].…”
Section: Discussionmentioning
confidence: 99%
“…The strain sensors proposed in [16,26] had good mechanical stability and a high measurement factor. A soft multi-axis force sensor based on an LM microchannel array could detect multi-directional force [59]. A wearable tactile sensor based on LM (Galinstan) had high flexibility and stretchability, and could sense temperature and contact force simultaneously [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A valuable demonstration of this type of sensor is shown in Figure 12C, where researchers were able to code American Sign Language to hand gestures via a resistive sensing device. Injection‐based LMPCs can also deform with more predictability due to the simplicity of the traces, making them excellent for accurately detecting forces and pressures 171,172 . Furthermore, several recent studies have shown LMPCs potential for thermal‐resistive sensing.…”
Section: Electronic Applicationsmentioning
confidence: 99%
“…Injectionbased LMPCs can also deform with more predictability due to the simplicity of the traces, making them excellent for accurately detecting forces and pressures. 171,172 Furthermore, several recent studies have shown LMPCs potential for thermal-resistive sensing. While remaining both stretchable and conductive, these composites experience magnitudes of change in resistance when exposed to temperature changes, highlighting their potential for overheating protection and other thermally driven smart devices.…”
Section: Electronic Applicationsmentioning
confidence: 99%